Fennel-growth story in India (MSW Management Journal, 2025)
India is a leading producer and exporter of fennel. The demand for fennel is increasing as the awareness of its medicinal benefits is gaining grounds. This paper attempts to understand the production and demand for Indian Fennel. We have also tried to empirically measure the growth trend of fennel production and its export from India. The calculation of instability index respective variables helps us to understand the crux of challenges for fennel in India. Few case studies are also included to show how continuous research are improving the volume and quality of fennel production. The paper concludes with progressive suggestions.